Adorno contra Simmel. Some notes - Giannakopoulou, Georgia (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This essay provides a brief overview of first-generation Frankfurt School reception of Georg Simmel’s work with focus on Theodor W. Adorno’s evaluation of Simmel’s sociology. In presenting a collection of direct notes from part of Adorno’s writings, the essay underlines Adorno’s seemingly ambivalent but predominantly negative and often insulting comments on Simmel thus distancing him from Walter Benjamin and Siegfried Kracauer whose works were self-admittedly influenced by Simmel, and bringing him closer to Ernst Bloch and Georg Lukács whose writings largely ‘renounced’ and often damaged Simmel’s legacy.